A fixed point theorem for mappings satisfying cyclical contractive conditions in (3,2)-W-symmetrizable spaces - Dimovski, Tomi; Dimovski, Donco (Faculty of Science, University of Kragujevac, Kragujevac, Serbia, 2023)
In this paper we are concerned with (3, 2)-symmetrics and (3, 2)-W-symmetrizable spaces. First we give the basic definitions, the notation, some examples and elementary results about these spaces, then we prove the existence of a fixed point for self mappings satisfying cyclical contractive conditions in (3, 2)-W-symmetrizable spaces.